基于并联机器人的柔性装配工装构型精度综合 - 石宏; 朱宁; 李伟楠; 李楠 (Jixie Chuandong, 2014)
A flexible fixture configuration for Aero-engine digital assembly is designed.Then aiming at the geometric feature of 3-UPU parallel mechanism,the error model is built considering universal hinge and rod length.Monte Carlo’s methods are adopted to analyze the influence on end executor error of rod length error and the universal vice clearance.Using particle swarm optimization based on interior point penalty function algorithm,accuracy synthesis is carried out according to the maximum pose error of end executor and objective function based on manufacturing cost minimum,the manufacturing tolerance of the parts is reasonable to determine,and a reference is provided for the development of prototype.